2021
DOI: 10.1007/s10653-021-00831-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of NO2 on outpatient visits for dermatologic diseases in Xinxiang, China: a time-series study

Abstract: Objectives As the largest organ of the human body, the skin is the major exposure route of NO 2. However, the evidence for a relationship between NO 2 exposure and dermatologic diseases (DMs) is limited. This time-series study was conducted to assess the shortterm effect of nitrogen dioxide (NO 2) exposure on DMs outpatient visits in Xinxiang, China. Methods Daily recordings of NO 2 concentrations, meteorological data, and the outpatient visits data for DMs were collected in Xinxiang from January 1st, 2015, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Chao et al have shown that short-term exposure to NO 2 increases patient visits in relation to psoriasis. (25) The toxic effect of NO 2 is in line with the results of several epidemiologic studies that have reported correlations between NO 2 and other skin diseases, including vitiligo (25), atopic eczema(26), and acne (27). From a physiological perspective, NO 2 can act as an oxidative stressor that produces free radicals in cells(28), increases trans-epidermal water loss, and damages the skin barrier function in keratinocytes.…”
Section: Discussionsupporting
confidence: 62%
“…Chao et al have shown that short-term exposure to NO 2 increases patient visits in relation to psoriasis. (25) The toxic effect of NO 2 is in line with the results of several epidemiologic studies that have reported correlations between NO 2 and other skin diseases, including vitiligo (25), atopic eczema(26), and acne (27). From a physiological perspective, NO 2 can act as an oxidative stressor that produces free radicals in cells(28), increases trans-epidermal water loss, and damages the skin barrier function in keratinocytes.…”
Section: Discussionsupporting
confidence: 62%
“…This result supports our hypothesis that the effect of NO2 on psoriasis is acute because a 10-µg m -3 increase in NO2 concentration (lag 0 day) was associated with a 3.1% (95% CI:2.5-3.7%) increase in the number of outpatient visits for psoriasis. A previous study (Chao et al, 2021) conducted in Xinxiang, China, reported that a 10μg m -3 increase in NO2 concentrations was associated with a 1.86% increase in the number of outpatient visits for multiple dermatologic diseases; for psoriasis, the increment risk of outpatient visits was 3.09% (95% CI:1.26-4.92%). The study (Chao et al, 2021) was conducted in an industrial city in North China with a relatively low population density, where the most considerable source of NO2 was coal combustion (Zong et al, 2018).…”
Section: Strengths Of the Studymentioning
confidence: 92%
“…A previous study (Chao et al, 2021) conducted in Xinxiang, China, reported that a 10μg m -3 increase in NO2 concentrations was associated with a 1.86% increase in the number of outpatient visits for multiple dermatologic diseases; for psoriasis, the increment risk of outpatient visits was 3.09% (95% CI:1.26-4.92%). The study (Chao et al, 2021) was conducted in an industrial city in North China with a relatively low population density, where the most considerable source of NO2 was coal combustion (Zong et al, 2018). Our study was conducted in rapidly urbanizing areas with high population densities in China, where NO2 is mainly derived from vehicular-and household-related emissions (Shao et al, 2009).…”
Section: Strengths Of the Studymentioning
confidence: 92%
See 1 more Smart Citation
“…A time-series quasi-Poisson generalized additive model was introduced to verify the relationships between ambient air pollution and children's outpatient visits. According to the results of previous time-series studies (25,26), several covariates were adjusted in the model. In this main smoothing model, degrees of freedom (df) were set on the basis of previous studies (24, 27):…”
Section: Statistical Analysesmentioning
confidence: 99%